A helping HAND: therapeutic potential of MAGL inhibition against HIV-1-associated neuroinflammation - League, Alexis F.; Yadav-Samudrala, Barkha J.; Kolagani, Ramya; Cline, Calista A.; Jacobs, Ian R.; Manke, Jonathan; Niphakis, Micah J.; Cravatt, Benjamin F.; Lichtman, Aron H.; Ignatowska-Jankowska, Bogna M.; Fitting, Sylvia (Frontiers in Immunology, 2024)
Background Human immunodeficiency virus (HIV) affects nearly 40 million people globally, with roughly 80% of all people living with HIV receiving antiretroviral therapy. Antiretroviral treatment suppresses viral load in peripheral tissues but does not effectively penetrate the blood-brain barrier. Thus, viral reservoirs persist in the central nervous system and continue to produce low levels of inflammatory factors and early viral proteins, including the transactivator of transcription (Tat). HIV Tat is known to contribute to chronic neuroinflammation and synaptodendritic damage, which is associated with the development of cognitive, motor, and/or mood problems, collectively known as HIV-associated neurocognitive disorders (HAND). Cannabinoid anti-inflammatory effects are well documented, but therapeutic utility of cannabis remains limited due to its psychotropic effects, including alterations within brain regions encoding reward processing and motivation, such as the nucleus accumbens. Alternatively, inhibiting monoacylglycerol lipase (MAGL) has demonstrated therapeutic potential through interactions with the endocannabinoid system. Methods The present study utilized a reward-related operant behavioral task to quantify motivated behavior in female Tat transgenic mice treated with vehicle or MAGL inhibitor MJN110 (1 mg/kg). Brain tissue was collected to assess dendritic injury and neuroinflammatory profiles, including dendritic microtubule-associated protein (MAP2ab) intensity, microglia density, microglia morphology, astrocyte density, astrocytic interleukin-1ß (IL-1ß) colocalization, and various lipid mediators. Results No significant behavioral differences were observed; however, MJN110 protected against Tat-induced dendritic injury by significantly upregulating MAP2ab intensity in the nucleus accumbens and in the infralimbic cortex of Tat(+) mice. No or only minor effects were noted for Iba-1+ microglia density and/or microglia morphology. Further, Tat increased GFAP+ astrocyte density in the infralimbic cortex and GFAP+ astrocytic IL-1ß colocalization in the nucleus accumbens, with MJN110 significantly reducing these measures in Tat(+) subjects. Lastly, selected HETE-related inflammatory lipid mediators in the striatum were downregulated by chronic MJN110 treatment. Conclusions These findings demonstrate anti-inflammatory and neuroprotective properties of MJN110 without cannabimimetic behavioral effects and suggest a promising alternative to cannabis for managing neuroinflammation.